Looking Upstream and Downstream in Entrepreneurial Cognition: Replicating and Extending the Busenitz and Barney (1997) Study. (22nd February 2016) - Arend, Richard J.; Cao, Xian; Grego‐Nagel, Anne; Im, Junyon; Yang, Xiaoming; Canavati, Sergio
Abstract : We revisit the assertion that entrepreneurs are uniquely characterized in their ways of thinking; specifically being relatively more prone to the overconfidence bias and the representativeness heuristic in their decision‐making. We replicate an earlier seminal study in entrepreneurial cognition, with a wider and more current survey. We then extend that analysis by investigating whether such "different thinking" leads to different (i.e., less rational) choices and different (i.e., worse) firm performance. Given the expected differences, we also investigate whether there exist other factors that affect the use of such biases and heuristics, to control their effects on focal outcomes.